Proanthocyanidins delaying the premature ovarian insufficiency through regulatory sirt1-p53-p21 signaling pathway in female germline stem cells - Wenbo Wu; Mengying Bai; Wenli Hong; Shuyi Ling; Yuan Li; Yuqing Dai; Ruoxin Weng; Haifeng Wu; Chongyang Ren; Liujuan Zhang; Ziqiong Zhou; Zhisheng Zhong; et al. (Journal of Ovarian Research)
Abstract Background As women age, their ovarian follicle pool naturally declines. However, female germline stem cells (FGSCs) possess a unique ability to differentiate into oocytes and continuously self-renew, providing an effective means of delaying ovarian aging by replenishing the primordial follicle pool. Therefore, activating FGSCs is critical in reshaping and safeguarding ovarian function. Methods In this study, we investigated the biological activity of proanthocyanidins (PACs), natural antioxidants that exhibit anti-aging and anti-inflammatory properties beneficial for both male and female reproduction. Our in vivo and in vitro experiments demonstrate that PACs promote FGSCs proliferation while delaying ovarian aging. Results PACs increase the number of primordial follicles, primary follicles, corpus luteum while reducing cystic follicles, and elevate estradiol (E2) levels along with anti-mullerian hormone (AMH) concentration levels in mice. Additionally, PACs significantly boost FGSCs proliferation time- and dose-dependently by upregulating mRNA & protein expressions for FGSCs-specific markers such as MVH and OCT4 while downregulating p53/p21 via activation of silent information regulator 1(Sirt1) signaling pathway. The effects of PACs on FGCSs were found to be impeded by the Sirt1 inhibitor EX527. Conclusion PACS delay premature ovarian insufficiency (POI) through regulating the Sirt1-p53-p21 signaling pathway involving FGSCs.